Effectiveness of Digital Consultation in Orthotic and Prosthetic Services: A Systematic Review - Gusma, Ellysa Okky; Sunarto, Gatot; Adityasiwi, Gian Lisuari; Kristina, Hana (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2026)
Background: Orthotic and prosthetic services are an important part of rehabilitation; however, access and continuity of care are often constrained by geographical distance, workforce shortages, and administrative barriers, particularly in centralized service models. Digital consultation and telehealth offer potential solutions by streamlining workflows and enhancing patient preparedness. However, empirical evidence in O&P remains limited. Objective: This study synthesizes evidence on the implementation and effects of digital consultation in O&P, including access, continuity of care, efficiency, transparency, patient-centered outcomes, and key barriers and facilitators. Methods: A systematic review was conducted in accordance with the PRISMA Statement. Searches were performed in PubMed/MEDLINE, Scopus, Web of Science, Google Scholar, and national journal portals from January 2016 to January 2026. Two reviewers independently screened studies, extracted data, and assessed methodological quality. Narrative synthesis was applied due to heterogeneity. Results: Seven studies (2020-2026) were included (one high-quality and six moderate-quality studies). Interventions included WhatsApp-based pre-visit consultations, service-monitoring systems, telehealth via video/telephone, and mobile O&P service delivery. Digital consultation improved administrative and clinical readiness, supported access and continuity of care, enhanced efficiency and process transparency, and was associated with high levels of patient satisfaction. However, physical assessment remained necessary at specific stages of care. The main barriers included limited internet connectivity, unequal access to digital devices, workforce readiness challenges, and inadequate integration of health information systems. Conclusion: Digital consultation can enhance the O&P services when integrated into routine workflows supported by integrated information systems.